Karakter Keberagamaan di Java Pasca Geertz - Gutomo Bayu Aji (LIPI Press, 2020)
Karakter keberagaman Geertz yang sering digunakan sebagai gambaran situasi keagamaan di Indonesia telah berubah secara drastis setelah peristiwa politik tahun 1965. Konteks perang dingin yang menggunakan Wahabi-salafisme sebagai instrumen pengendalian komunisme telah menciptakan tekanan dan ancaman yang memungkinkan terbentuknya otoritarianisme keagamaan. Dalam struktur dominasi dan sub-ordinasi, pemerliharaan otoritarianisme itu dilakukan melalui pemeliharaan agama resmi yang diakui pemerintah dan penggunaan diskursus toleransi sebagai instrumen hegemoni terhadap kepercayaan-kepercayaan sub-ordinat. Gus Dur merupakan aktor yang memainkan peranan penting dalam pembongkaran otoritarianisme itu. Tetapi sepeninggalnya, kecenderungan otoritarianisme semakin mengeras ketika bersinggungan dengan oligarkhi yang menguasai sumber daya ekonomi-politik. Kelompok pedesaan terutama petani kecil dan buruh tani adalah yang paling dipinggirkan dengan instrumen penjinakan ganda yaitu revolusi hijau dan otoritarianisme keagamaan. Kata kunci: keberagaman, otoritarianisme keagamaan, toleransi, dialog agama, rekonsiliasi, marjinal. Abstract Geertz’s religious characterization underwent drastic change since the ‘65 event. Western influences and the use of Wahabi-salafism as instruments of religious politics have changed the open model of religious life. After that event, the model of religious life turns into closed; formed on the basis of a political security agenda and limited to five official religions.. This article views the model as the basis for the formation of an authoritarian religious character, among others, which gives space to modernists to control the political infrastructure of religious and state religious resources, strengthen limited official religious arrangements, allow pressures and threats to work on religious conversion, purification of traditions and labeling untruth. In addition, the model is used to produce a discourse of tolerance which has the following tendencies: the discourse of tolerance originating from Western political philosophy is contradictory to the religious norms that are growing in Indonesian society, and the discourse operates in a limited manner among official religions as the dominant discourse that is dominant creating formal-exclusivism that strengthens the authoritarian religious character. Key words: diversity, authoritarianism, tolerance, religious dialogue, reconciliation, marginality